IR4.0: unmanned store apps - Saidatul Rahah Hamidi; Muhammad Afiq Muhamad Yusof; Shuhaida Mohamed Shuhidan; Shamsiah Abd Kadir (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The Internet of Things (IoT) is predicted to be one of the major megatrends in technology that applies worldwide including in Malaysia. Current advantages and expectations of using a connected device has become a reason to use applications in many areas, including the field of retail industry. The evolvement of technology has changed the retail landscape that replaces the manpower in their operations to improve the efficiency, quality and work ethics. Hence, this paper discussed comparative study of technology innovation applied and process flow in unmanned store from different country. Next, prototype of unmanned store apps was designed according to the most preferred technology based on the comparative study. IoT retailer model can be used to improve the retail experience for the customers. Thus, it may perform strategic marketing and gain retail intelligence. Besides, the revolution of using technology in this retail industry is contributing towards Industry 4.0 through digital transformation.